2013
DOI: 10.9775/kvfd.2013.8747
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Different Progesterone Analogues and GnRH on Reproductive Parameters in Nulliparous Saanen Goats at the End of the Transition Period

Abstract: The objective of this study was to compare the efficacy of diff erent estrus synchronization protocols on reproductive parameters in nulliparous Saanen goats at the end of the transition period. In this experiment, 71 nulliparous Saanen does were used and divided into four treatment groups as norgestomet implant plus GnRH (Imp-G), norgestomet implant (Imp), FGA sponge plus GnRH (Spo-G), and FGA sponge (Spo). The progestagen treatments were administered for 11 days. At progestagen withdrawal, all does were inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(60 reference statements)
0
1
1
Order By: Relevance
“…In the same way, Uslu and Gülyüz [33] stated that GnRH injection after breeding has a positive effect on the pregnancy rate. In contrast, some studies have shown that hCG and GnRH injection after breeding are not beneficial for increasing fertility or the pregnancy rate [2,4,26,31]. This study does not support the hypothesis that GnRH treatment at breeding and after breeding prevents embryonic loss and improves reproductive performance.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In the same way, Uslu and Gülyüz [33] stated that GnRH injection after breeding has a positive effect on the pregnancy rate. In contrast, some studies have shown that hCG and GnRH injection after breeding are not beneficial for increasing fertility or the pregnancy rate [2,4,26,31]. This study does not support the hypothesis that GnRH treatment at breeding and after breeding prevents embryonic loss and improves reproductive performance.…”
Section: Discussioncontrasting
confidence: 74%
“…Blood samples for progesterone measurement were taken into anticoagulated tubes 4 by jugular vena puncturing on days 3, 6, 7, 10, 13, 16 and 19 days after breeding from 10 randomly chosen goats in all groups. Blood sampling was also performed for all goats on day 21.…”
Section: Serum Samples and Progesterone Measurementsmentioning
confidence: 99%